هاوكاری مرۆیی ڕێكخراوه‌ نێودەوڵەتییەکان بۆ باشورى کوردستان لە1991دا - كه‌ریم, پ.ی.د. هێرش عه‌بدوڵڵا حه‌مه‌; محمد, م.ي. سامان مجيد (Sulaimani Journal for Humanities, 2023)
This resarch explained the most important period in the history of Iraqi Kurdistan. it is the first study in human history in this regard. , the researcher describes the types and amounts of humanitarian aid provided by governmental and non-governmental organizations to Iraqi Kurdish displaced people on the borders of Turkey and Iran in 1991. After the adoption of Resolution 688, the UN appeal to countries, humanitarian organizations and voluntary groups, which dozens of international humanitarian organizations went to the border areas of Turkey and Iran to help the Kurdish displaced people . These organizations played an important role in the relief efforts, providing humanitarian assist ance and basic necessities for the displaced people. Most of these organizations were medical, which reflected the situation of the Kurdish displaced people. Then, the United Nations continued the emergency efforts and delivering hundreds of tons of food and medical supplies to the displaced people. as well as Especially, after returned the coalition troops and hand over relief efforts to the United Nations. They reconstructed of many service institutions in Kurdistan and again trying to return people to their villages and areas. The main question of this research is: What is the type and quantity of humanitarian assistance provided by international organizations to refugees in southern Kurdistan in 1991? . The content of this research consists of four topics: the first topic is the situation of the refugees in South Kurdistan in 1991, . The second is: the humanitarian assistance of NGOs to displaced people on the Turkish borders. The third is: the humanitarian assistance of international organizations to displaced people on the Iranian border. The Fourth is: Humanitarian Assistance of Government Organizations (UN) to Kurdistan.
Keywords: Keywords (humanitarian aid; international organizations; governmental organizations; NGOs; displaced Kurds; TurkishIranian borders)